A case of adrenal Cushing's syndrome and primary hyperparathyroidism due to an atypical parathyroid adenoma. (July 2021) - Newman, Christine; Costello, Maria; Casey, Mary; Davern, Recie; Dinneen, Kate; Lowery, Aoife; McHale, Teresa; O'Shea, Paula M; Quinn, Anne M; Bell, Marcia
Cushing's syndrome is a rare disorder of cortisol excess and is associated with significant morbidity and mortality. Hypercalcaemia due to hyperparathyroidism is a common condition; however, in 10% of young patients, it is associated with other endocrinopathies and occurs due to a genetic variant [e.g. multiple endocrine neoplasia (MEN) type 1 (MEN1), MEN2 or MEN4]. We report the case of a 31-year-old woman who was referred to the endocrinology out-patient service with an 8-month history of hirsutism, amenorrhoea and weight gain. Her biochemical work up was significant for adrenocorticotropic hormone (ACTH)-independent Cushing's syndrome. Radiological investigations revealed an adrenal adenoma. During investigation she was also found to have primary hyperparathyroidism due to a parathyroid adenoma. Pre-operatively, the patient was commenced on metyrapone and both her adrenal and parathyroid lesions were resected successfully. There were several concerning findings on initial examination of the parathyroid tumour, including possible extension of the tumour through the capsule and vascular invasion; however, following extensive review, it was ultimately defined as an adenoma. Given the unusual presence of two endocrinopathies in a young patient, she subsequently underwent genetic testing. Analysis of multiple genes did not reveal any pathogenic variants. The patient is currently clinically well, with a normal adjusted calcium and no clinical features of cortisol excess. She will require long-term follow up for recurrence of both hypercalcaemia and hypercortisolaemia.